Penakaran Dampak Emisi Debu PLTU Batubara 600 MWe dengan Metode Pendekatan Life Cycle Assessment (LCA) - , SAIPUL BAHRI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The coal fired power plant of Cilacap can be relied to fulfill the electrical network in Java-Madura-Bali. Since 2006 until 2012, the community has been complaint for dust (particulate) emission from the plant activities that indicated could polluted the environment especially for coal dust emission from the overhauling loaded. The aim to know the coal transportation route influence from Tanjung Intan harbour and power plant's port of emission dust that spreaded to the environment, the effect to the human and environment health also the way that can be used to decrease the emission, using Life Cycle Assessment (LCA) method. The study of LCA has done since the arrival of coal at Cilacap to ashes that coming out from stack for 600 MWe per hour. The study using gate to gate approachment, suitable with the LCA frame work in ISO 14040 (2006) which is consist of the goal and scope definition, inventory analysis, impact assessment and interpretation. From the inventory analysis, it is known that the amount of particulate emission from the overhauling loaded through the Tanjung Intan harbour are 12,3 kg (TSP), 5,73 kg (PM 10) and 0,629 kg (PM 2,5) while through the plantâs port are 0,799 kg (TSP), 0,631 kg (PM 10) and 0,0568 kg (PM 2,5). From the impact assessment, itâs known that the overhauling loaded stripe through the Tanjung Intan harbour is more dominant compare with the plantâs port with deviation of: (1) The total effect of toxicological matters (non carcinogen) in particulate is 2,28E-05 DALY, (2) the effect of carcinogen is 2,13E-06 DALY, (3) the effect of respiratory disturbance is 3,67E-03 DALY, (4) the effect of aquatic ecotoxicity is 4,1E-01 PDF*m2*year, and (5) the effect of terrestrial eco toxicity is 123,5PDF*m2 *year. If the overhauling loaded from Tanjung Intan harbour remain to be done, advisable to replace truck by train. The usage of train could reduced the amount of dust pollution as 7,4E-01 kg (TSP),6,3E-01 kg (PM 10) dan 5,68E-02 kg (PM 2,5) so the total effect to the human and environmental health can be reduced significantly.